Perfluoroalkyl acids in pregnant women from Nunavik (Quebec, Canada) : trends in exposure and associations with country foods consumption - Caron-Beaudoin, Élyse; Ayotte, Pierre; Blanchette, Caty; Muckle, Gina; Avard, Ellen; Ricard, Sylvie; Lemire, Mélanie (Environment International, 2022)
Objectives From 2004 to 2017, 279 pregnant Inuit women were recruited as part of biomonitoring projects in Nunavik. Our goal was to evaluate: (i) time-trends in plasma/serum PFAAs levels in pregnant Nunavimmiut women between 2004 and 2017; (ii) compare plasma/serum PFAAs levels in Nunavimmiut women in 2016–2017 to those measured in women of childbearing age in the Canadian Health Measure Survey (CHMS); and (iii) evaluate the associations of PFAAs levels with the consumption of country foods and pregnancy and maternal characteristics during pregnancy in the 97 participants recruited in 2016–2017. Methods Individual blood sample were collected for serum or plasma PFAAs (PFOS, PFOA, pentafluorobenzoic acid (PFBA), perfluorohexanoic acid (PFHxA), perfluorobutanesulfonic acid (PFBS), perfluorohexane-1-sulfonic acid (PFHxS), PFNA, PFDA, PFUdA) analyses. Socio-demographic data, pregnancy and maternal characteristics and country foods consumption were documented using a questionnaire. Omega-3 and −6 polyunsaturated fatty acids (PUFA) were measured in red blood cell membranes and their ratio used as a biomarker of marine country foods consumption. Time-trends in PFAAs levels were evaluated using ANCOVA models adjusted for relevant co-variables. Serum/plasma levels of PFAAs in the 97 pregnant women aged 16 to 40 years old and recruited in 2016–2017 were compared to those measured in women aged 18 to 40 years old from the CHMS cycle 5 (2016–2017) using the geometric means (GM) and 95% confidence intervals (95% CI). Multivariate regression analyses were performed to examine associations between concentrations of PFAAs and country foods consumption data. Results Statistically-significant downward time trends were noted for concentrations of PFOS, PFOA and PFHxS in pregnant Nunavik women between 2004 and 2017. Conversely, between 2011 and 2016–2017, PFNA, PFDA and PFUdA maternal serum levels increased by 19, 13 and 21% respectively. Among participants in 2016–2017, mean concentrations for PFNA (GM: 2.4 μg/L), PFDA (0.53 μg/L) ...